TEKNIK BERMAIN PERAN PADA LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN SELF-ESTEEM - Awlawi, Addahri Hafidz (Universitas Negeri Padang, 2013)
The discovery from this research are: (1) condition of self-esteem of high school students in particular 8 students experiment is still relatively low. (2) There were significant differences between students’ Self-Esteem in pre-test and post-test from Experimental group. (3) There was no significant defferences between Self-Esteem in pre-test and post-test from control group students. (4) There were significant differences between students’ Self–Esteem in post-test from Control group and post-test from Experimental group. Based on the discovery above, we can conclude that implemeting role playing is effective to be used in group guidance service to increase students’ Self-Esteem. This research shows that is important to apply role playing in group guidance service that espoused with supervision from teacher and counselor at school, so that it can increase students’ Self-Esteem.